The forward bias in the ECU: Peso risks vs. fads and fashions - Sercu, Piet; Vinaimont, Tom (Journal of Banking & Finance, 2006)
Forward rates of European currencies against the private and official ECU exhibit a bias similar to the one found in other data: the Cumby–Obstfeld–Fama (COF) regression coefficients are systematically below unity, and two thirds of them are negative. We use the discount of the private ECU relative to the official ECU as a measure of market scepticism or mistrust. In one view, this sentiment is based on peso risk: fears of realignments, and possibly also the risk of a meltdown of the private ECU relative to the official one. Alternatively, the discount just reflects fads and fashions. Dichotomizing the data on the basis of the size of the discount in the private ECU, we find that the COF beta strongly depends on the degree of mistrust and that the negative COF coefficients are generated by typically less than 20% of the data. But the pattern fits the fads and fashion view better than the peso theory. If the sentiment factor contains a conventional risk premium at all, then this risk premium is definitely not the one predicted by Bansal [Bansal, R., 1997. An exploration of the forward premium puzzle in currency markets. Review of Financial Studies 10, 369–403]. Nor is the sentiment factor proxying for Huisman et al.’s [Huisman, R., Koedijk, K., Kool, C., Nissen, F., 1998. Extreme support for uncovered interest parity. Journal of International Money and Finance 17, 211–228] transaction-cost effects.